Pengaruh Kebijakan Modal Kerja Terhadap Profitabilitas pada Perusahaan Hotel dan Restoran yang Terdaftar di Bursa Efek Indonesia (BEI) - Singa, Yenli Junita; Bailusy, Muhsin N; Taslim, Fadli Ali (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2022)
ABSTRACTObjective: The objectives in this study are: 1) Knowing and analyzing the effect of working capital turnover on profitability; 2) Knowing and analyzing the effect of cash turnover on profitability; 3) Knowing and analyzing the influence of accounts receivable turnover on profitability; 4) Knowing and analyzing the effect of inventory turnover on profitability; and 5) Knowing and analyzing the effect of working capital funding on profitability. The object and research are hotel and restaurant companies listed on the Indonesia Stock Exchange in the 2015-2019 period. There are 21 hotel and restaurant companies. Based on the results of the sample selection in accordance with certain criteria, 12 companies are eligible for the sample.Methodology: Data analysis techniques were performed using statistical tests using multiple linear regression with the help of the IBM Statistical Package for Social Science (SPSS) version 21.Finding: H2, H3, H4, and H5 are H1 are rejected, while H1 accepted at the 5% confidence level.Conclusion: The results showed that: 1) Capital turnover has a significant positive effect on profitability; 2) Cash turnover does not have a significant effect on profitability; 3) Receivables turnover has a significant effect on profitability; 4) Inventory Turnover does not have a significant effect on profitability. The inventory turnover rate shows the speed of return of funds embedded in inventory; and 5) Working capital funding does not have a significant effect on profitability.